História e memória: Comunidade Quilombola Campo Verde - SILVA, Elizabete Trindade da (2022)
This article aims to show the importance of the songs written by the people of the quilombola community of Campo Verde and how people identify themselves through these songs, establishing an identity and showing resistance, struggles and conquests for their rights. To carry out this research, it was necessary to use sources such as: interviews with residents, legends, photos and musical lyrics. For that, I made an analysis of the founding history of the city of Concórdia do Pará, its geographical location, the founding history of the Campo Verde community in the period from 1979 to the present. In the case of a quilombola community, this research also includes a bit of the history of the foundation of ARQUINEC (Associação dos Remanescentes de Quilombo Nova Esperança de Concórdia do Pará).